Applying the Bible - Kuhatschek, Jack, 1949- (Grand Rapids, MI Zondervan, 1996)
Includes bibliographical references.
Originally published: "Taking the guesswork out of applying the Bible", Downers Grove, IL, IVP, c. 1990`
Keywords: Bible -- use